Daytime radiative cooling: To what extent it enhances office cooling system performance in comparison to night cooling in semi-arid climate?. (March 2020) - Katramiz, Elvire; Ghaddar, Nesreen; Ghali, Kamel
Abstract: This work investigates the performance of a novel passive cooling system for an office space in hot and dry climate. A daytime radiative cooling (RC) panel was coupled with a phase change material (PCM) storage tank system where the nocturnal radiative cooling power was used to regenerate the PCM during nighttime and the diurnal power during daytime was used to reduce the window temperature. To predict system operation, a mathematical model was developed integrating the hydronic RC panel model, water/PCM system heat exchange model, and ventilated window and space model. The developed model was applied to a case study in Beqaa area of inland Lebanon. It was found that the use of diurnal RC panel power for window cooling reduced the storage system size by 12.3% in comparison to the case where only night RC panel was used. The window cooling reduced the radiation asymmetry in the office and resulted in cost savings of 10% when operated during the summer. Highlights: Model a passive cooling system with daytime radiative cooling for an office in semi‐arid climate. Combine radiative cooling panel with phase change material (PCM) storage tank and window cooling system. The daytime cooling power reduced the window load by 32% and radiant temperature asymmetry by 29%. The proposed system decreased the needed storage PCM mass by 12.3%.